Forensic nursing care: an analysis of knowledge and practices of portuguese nurses - Mota, Edene Melodie; Cunha, Madalena; Santos, Eduardo (Millenium - Journal of Education, Technologies, and Health, 2021)
Introduction: Cases of violence and trauma are constantly increasing in Portugal. The knowledge empowerment of the nursing teams is essential for the implementation of good practices in the forensic area so as to provide the person, whether victim, suspect or aggressor, with the necessary health, medico-legal and legal care, as well as the legal safety of nurses. Objective: To assess the practices and knowledge of Portuguese nurses about forensic nursing. Methods: Quantitative, descriptive-correlational, and cross-sectional study carried out with Portuguese nurses. Data were collected using the General Forensic Nursing Questionnaire by Cunha & Libório (Libório, 2012). The study obtained a favorable approval by the Ethics Committee of the Ethics Committee of the Polytechnic Institute of Viseu, no. 10/ SUB/ 2021, and by the Ordem dos Enfermeiros, whose collaboration in the disclosure took place between May 6, 2021 and May 31, 2021. Results: 403 nurses were included, representing 0.55% of the universe of nurses registered in the Ordem dos Enfermeiros. Most of them were female (81.1%) and had a mean age of 41.18 years (±9.71). They consider that they have low knowledge even though they perform adequate practices in the field of forensic nursing. The available training is insufficient even though they consider it very important (90.6%). It was found that the frequency of training and the existence of protocols have an impact on the level of knowledge and quality of forensic practices (p<0.05). Conclusion: Health services lack forensic experts, and their absence jeopardizes rigorous procedures, the chain of custody and consequently the medico-legal rights of the victim. The adoption of academic curricula that include forensic content, training and team building may improve the forensic nursing care provided to the community.